1997
DOI: 10.1103/physrevlett.79.4246
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Quantum Hall Effect Measurements at Zero g Factor

Abstract: Fractional quantum Hall effect energy gaps have been measured as a function of Zeeman energy. The gap at n 1͞3 decreases as the g factor is reduced by hydrostatic pressure. This behavior is similar to that at n 1 and shows that the excitations are spinlike. At small Zeeman energy, the excitation is consistent with the reversal of 3 spins and may be interpreted as a small composite Skyrmion. At 20 kbar, where g has changed sign, the 1͞3 gap appears to increase again. [S0031-9007(97)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 24 publications
4
77
0
1
Order By: Relevance
“…Thus it belongs to the reversed sequence of the (3, 3, 2) FQH state. Transitions between the singlet state at ν = 2/3 and the fully polarized state at the same filling factor have also been observed [11]. The excitation spectrum of the ν = 2/3 spin singlet state can be constructed analogously.…”
Section: Electron Statesmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus it belongs to the reversed sequence of the (3, 3, 2) FQH state. Transitions between the singlet state at ν = 2/3 and the fully polarized state at the same filling factor have also been observed [11]. The excitation spectrum of the ν = 2/3 spin singlet state can be constructed analogously.…”
Section: Electron Statesmentioning
confidence: 94%
“…In particular we computed the tunneling exponents for the spin singlet states that have been observed experimentally [11], whose filling fractions are ν = 2/3, 2/5, 4/7, 4/9. For instance , for electron tunneling between two 2/3 states we found that the tunneling current obeys Ohms law.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in the integral quantum Hall regime, skyrmions at ν = 1 3 (proposed by Kamilla et al 47 ) were only recently detected in a transport experiment, 48,49 thanks to a sufficient reduction of the Zeeman gap E Z by means of hydrostatic pressure. The subsequent numerical calculation 50 also indicated the formation of small skyrmions and anti-skyrmions in finite-size fractional quantum Hall systems.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another type of quantum Hall ferromagnetism occurs in monolayer systems if single particle states in different Landau level with different spins are tuned to energetic coincidence as it can be done by tilting the magnetic field 38,31 . An important connection between electron spin quantum Hall ferromagnetism in monolayers and spin-orbit effects arises from studies of the dependence of the effective g-factor on the lattice constant of the semiconductor material which can be varied by applying external pressure [39][40][41][42] .…”
Section: Introductionmentioning
confidence: 99%